HUBUNGAN MINAT MEMBACA DAN KEMAMPUAN MENULIS TEKS EKSPOSISI BAHASA INDONESIA SISWA KELAS X MAN 2 KOTA BENGKULU - Sri Wilujeng Widiastuti (Universitas Bengkulu, 2016)
The purpose of this study to explain interest in reading , the ability to write text exposition , and the relationship between interest in reading with the ability to write text exposition Indonesian Class X MAN 2 Kota Bengkulu . This study uses descriptive correlational . The population in this study are all students of class X MAN 2 Kota Bengkulu . Samples were taken using random sampling techniques or random sample , with a sample of 36 students. Instrument data capture using documentation and questionnaires . From the research results can be described that 1 ) the average interest of the students' reading interest category with an average value of 3.09 , 2 ) the ability to write text exposition of students categorized either with a mean value rata76,2 , 3 ) there is a relationship between interest in reading the ability to write text Indonesian exposition with a correlation value of r count 0,53? r tables = 0.32 , meaning that its interpretation is rather low so that the relationship was not significant.Kata Kunci: Interests in Reading, Writing and Text Exposition